Behavior of Concrete-Filled Steel Tube Columns under Fire - AL-Wsabi, Emad; Falah, Nabil (University of Science and Technology, Yemen, 2015)
This paper presents the results of a numerical study of fire resistance of concrete-filled steel tube (CFST) columns, using ABAQUS program. An analytical approach consisting of three sequential analytical steps, namely, fire analysis, heat transfer analysis, and stress analysis to predicting the behavior of CFST columns under fire loading. Those included nonlinear 3D finite element models for both heat transfer and stress analysis. The illustrative model is validated by means of comparison between the numerical output data and the experimental results available in the literature. The test is for the fire resistance of CFST column subjected to the standard ASTM fire and bearing axial compression. Hence, a good agreement had been observed between the numerical and experimental results. Therefore, the finite element models are able to predict the behavior of CFST columns under fire loading.